THU0123 Medication adherence and cost-related medication non-adherence in patients with rheumatoid arthritis, a mixed method study in iran. (12th June 2018) - Heidari, P.; Cross, W.; Nazarinia, M.; Crawford, K.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that often requires long term treatment with multiple medications. Medication adherence is essential in patients with RA to manage the disease. Objectives: This study aimed to assess medication adherence and cost-related medication non-adherence (CRN) among patients with RA in Shiraz, Iran from the perspective of patients and rheumatologists. Methods: A convergent parallel mixed method study was employed. A survey targeted RA patients attending the outpatient clinics in Shiraz. The survey collected demographic information followed by an assessment of adherence using the Compliance Questionnaire Rheumatology (CQR) 1 and featured 4 questions on CRN. 2 The cut-off point of 80% was used to identify patients as adherent or non-adherent. Semi-structured interviews were conducted with rheumatologists exploring their experiences in regard to medication adherence and its determinants. Descriptive data analysis of the surveys was undertaken using SPSS version 24. Interviews were transcribed and analysed using thematic analysis. Results: A total of 308 surveys were collected and 10 interviews were conducted. The majority of patients were female (86%), married (79.7%), living in urban areas (66.2%), housewives (73.1%), with no income (68.2%) and illiterate (41.9%). Six of the interviewed rheumatologists were male and participants had a mean of 8.6 years of experience as a physician. According to the CQR questionnaire; 59.7% of patients were considered non-adherent. In terms of cost, 26.3% of patients had not refilled their prescription; 52.1% had delayed refilling their prescription; 18.2% had skipped doses; or 18.5% had taken less medication to make the medication last longer. In contrast, the rheumatologists considered that the majority of their patients were adherent to their prescribed medication. However, they saw medication side effects, poor patient-doctor relationship and high costs of biologics as barriers of adherence. Surveys found that only 19.9% of patients were using biologic agents. This is in concordance with rheumatologists' discussion about high costs of biologics and they will not prescribe biologics because they know that the majority of patients cannot afford the medication. Conclusions: Although the findings of the survey suggested that medication adherence is sub-optimal among Iranian patients with RA, rheumatologists consider the majority of their patients as adherent. The high costs of the medication was found to contribute to medication non-adherence. Therefore, health policy makers should consider this issue while identifying the medication prices. References: [1] de Klerk E, et al. The compliance-questionnaire-rheumatology compared with electronic medication event monitoring: a validation study. The Journal of Rheumatology2003;30(11): 2469. [2] Soumerai SB, et al. Cost-related medication nonadherence among elderly and disabled medicare beneficiaries: A national survey 1 year before the medicare drug benefit. Archives of Internal Medicine2006;166(17): 1829–1835. Acknowledgements: We would like to thank the patients who agreed to participate in the study, the rheumatologists who gave their valuable time to be interviewed and a special thanks to Dr Mansour Hosseini and Dr Mehdi Kaffashan for their help with data collection Disclosure of Interest: None declared